AT1 Receptor Gene Polymorphisms in relation to Postprandial Lipemia - B. Klop; T. M. van den Berg; A. P. Rietveld; J. Chaves; J. T. Real; J. F. Ascaso; R. Carmena; J. W. F. Elte; Manuel Castro Cabezas (International Journal of Vascular Medicine)
Background. Recent data suggest that the renin-angiotensin system may be involved in triglyceride (TG) metabolism. We explored the effect of the common A1166C and C573T polymorphisms of the angiotensin II type 1 receptor (AT1R) gene on postprandial lipemia. Methods. Eighty-two subjects measured daytime capillary TG, and postprandial lipemia was estimated as incremental area under the TG curve. The C573T and A1166C polymorphisms of the AT1R gene were determined. Results. Postprandial lipemia was significantly higher in homozygous carriers of the 1166-C allele (9.39±8.36 mM*h/L) compared to homozygous carriers of the 1166-A allele (2.02±6.20 mM*h/L) (P<0.05). Postprandial lipemia was similar for the different C573T polymorphisms. Conclusion. The 1166-C allele of the AT1R gene seems to be associated with increased postprandial lipemia. These data confirm the earlier described relationships between the renin-angiotensin axis and triglyceride metabolism.